ON THE STATE MECHANISMS OF ENSURING SOCIAL POLICY IN THE REPUBLIC OF KAZAKHSTAN - Ayupova Z.K.; Kussainov D.U; Winston Nagan (Academic Journal of Physical and Chemical Sciences, 2019)
Thestate independence of the Republic of Kazakhstan means the problem of “building of strong lawabiding state with the socially oriented market economy”. The questions of social politics especially actual in the connection with the development of sovereign Kazakhstan, requiring the necessity of realization of new social politics in the conditions of political modernisation of the society. In all spheres of activity the value of the social politics increases from year to year. The state assumes social functions not simply from some good intentions, butthe result of public requirement in the extended social reproduction of population, changes of role of man in economy, production and realization of dependence of public progress. In these terms essence and maintenance of social politics change, the spheres of its action quite broad. The decision of social problems depends not only on the presence of sufficient financial resources, but also exactness of select strategy of realization of public policy. In this connection again the searches of new approaches are strict in the realization of effective social politics in the conditions of globalization of national economy.